2018
DOI: 10.1021/acs.jmedchem.8b01224
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Promotes Weight Loss in Diet-Induced Obesity by Inhibiting the Protein Tyrosine Phosphatases PTP1B and TCPTP in the Hypothalamus

Abstract: Celastrol is a natural pentacyclic triterpene used in traditional Chinese medicine with significant weight-lowering effects. Celastrol-administered mice at 100 μg/kg decrease food consumption and body weight via a leptin-dependent mechanism, yet its molecular targets in this pathway remain elusive. Here, we demonstrate in vivo that celastrol-induced weight loss is largely mediated by the inhibition of leptin negative regulators protein tyrosine phosphatase (PTP) 1B (PTP1B) and T-cell PTP (TCPTP) in the arcuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 68 publications
2
45
1
2
Order By: Relevance
“…In contrast to the study by Saito and colleagues [ 132 ], the anti-obesity action of celastrol was associated with reduced ER stress in the hypothalamus. Kyriakou and colleagues [ 134 ] have recently shown that deletion of hypothalamic leptin signaling inhibitors—PTP1B and TCPTP—successfully lowers body weight in diet-induced obese mice, supporting the concept that celastrol restores the control of energy balance through enhancing hypothalamic leptin sensitivity. Whether or not this is linked to lower ER stress or inflammation in the hypothalamus is not clear.…”
Section: Role Of Antioxidants/anti-inflammatory Agents In the Cnsmentioning
confidence: 97%
“…In contrast to the study by Saito and colleagues [ 132 ], the anti-obesity action of celastrol was associated with reduced ER stress in the hypothalamus. Kyriakou and colleagues [ 134 ] have recently shown that deletion of hypothalamic leptin signaling inhibitors—PTP1B and TCPTP—successfully lowers body weight in diet-induced obese mice, supporting the concept that celastrol restores the control of energy balance through enhancing hypothalamic leptin sensitivity. Whether or not this is linked to lower ER stress or inflammation in the hypothalamus is not clear.…”
Section: Role Of Antioxidants/anti-inflammatory Agents In the Cnsmentioning
confidence: 97%
“…In order to study the binding kinetics ( k on , k off rate constants) of the Sirt2–SirReal interaction by means of a method that does not require a labeled ligand, we made use of the DNA nanolever‐based switchSENSE ® technology . This method is sensitive enough to monitor the binding of an unlabeled small molecule to a surface‐tethered protein . In the experimental setup we used for our studies, Sirt2 was covalently bound to one strand of a double‐stranded short DNA nanolever grafted to the surface of a gold microelectrode.…”
Section: Resultsmentioning
confidence: 99%
“…[31] This method is sensitivee nough to monitort he binding of an unlabeled small molecule to as urface-tethered protein. [32] In the experimental setup we used for our studies, Sirt2 was covalently boundt o one strand of ad ouble-strandeds hort DNA nanolever grafted to the surface of ag old microelectrode.T he other strand is labeled with af luorescent dye, in this case Cy3 (Figure 2A). In general,s uch as etup can be used in two different measuring modes.…”
Section: Resultsmentioning
confidence: 99%